The glycosomal alkyl-dihydroxyacetonephosphate synthase TbADS is essential for the synthesis of ether glycerophospholipids in procyclic trypanosomes - Lee, Sungsu (Exp Parasitol, 2018)
Glycerophospholipids are the main constituents of the biological membranes in Trypanosoma brucei, which causes sleeping sickness in humans. The present work reports the characterization of the alkyl-dihydroxyacetonephosphate synthase TbADS that catalyzes the committed step in ether glycerophospholipid biosynthesis. TbADS localizes to the glycosomal lumen. TbADS complemented a null mutant of Leishmania major lacking alkyl-dihydroxyacetonephosphate synthase activity and restored the formation of normal form of the ether lipid based virulence factor lipophosphoglycan. Despite lacking alkyl-dihydroxyacetonephosphate synthase activity, a null mutant of TbADS in procyclic trypanosomes remained viable and exhibited normal growth. Comprehensive analysis of cellular glycerophospholipids showed that TbADS was involved in the biosynthesis of all ether glycerophospholipid species, primarily found in the PE and PC classes.